Approaching Things that Trigger Things: A Review of Three Shifts in the Character of Things and Their Implications for Design. - Wiberg, Mikael (Design Issues)
In this article I focus on the changing character of things. In doing so, I review and draw together a set of existing sources, and emerging strands and conceptions of design, to discuss three fundamental shifts that have profoundly changed the character of the things we surround ourselves with, and I discuss their implications for design. I contribute to existing design research by bringing these strands together, and by making this accessible in the form of the three shifts.